Clay induced aggregation of a tetra-cationic metalloporphyrin in Layer by Layer self assembled film. (December 2015) - Banik, Soma; Bhattacharjee, J.; Hussain, S.A.; Bhattacharjee, D.
Abstract: Porphyrins have a general tendency to form aggregates in ultrathin films. Also electrostatic adsorption of cationic porphyrins onto anionic nano clay platelets results in the flattening of porphyrin moieties. The flattening is evidenced by the red-shifting of Soret band with respect to the aqueous solution. In the present communication, we have studied the clay induced aggregation behaviour of a tetra-cationic metalloporphyrin Manganese (III) 5, 10, 15, 20-tetra (4 pyridyl)-21 H, 23 H-porphine chloride tetrakis (methochloride) (MnTMPyP) in Layer-by-Layer (LbL) self assembled film. The adsorption of dye molecules onto nano clay platelets resulted in the flattening of the meso substituent groups of the dye chromophore. In Layer-by-Layer ultrathin film, the flattened porphyrin molecules tagged nano clay platelets were further associated to form porphyrin aggregates. This has been clearly demonstrated from the UV–vis absorption spectroscopic studies. Atomic Force Microscopic (AFM) studies gave visual evidence of the association of organo-clay hybrid molecules in the LbL film. Graphical abstract: Highlights: Interaction of cationic metalloporphyrin MnTMPyP with anionic nano clay laponite. Flattening of MnTMPyP molecules onto nano clay platelets. Overlapping and tilted organization of MnTMPyP tagged clay platelets in LbL film. Formation of J-aggregated sites in LbL film by MnTMPyP tagged nano clay platelets.